Pengaruh Media Microblogging Threads Terhadap Kemampuan Menulis Teks Argumentasi Siswa Kelas XI SMA Parulian 2 Medan - Yosevin Nadeak; Sarma Panggabean; Eka Putri Saptari Wulan (Visi Sosial Humaniora, 2026)
This study aims to determine the impact of the use of the Microblogging Threads platform on students' ability to write argumentative texts. The methodology applied in this study is an experiment with a one-group pretest-posttest design. The population involved in this study were all students, with a sample size of 27 students. Data collection was carried out through an argumentative text writing ability test carried out before (pretest) and after (posttest) the treatment was given. Based on the data obtained from the study, the average pretest score was recorded at 46,59 in the very poor category, while the average posttest increased to 75.85 and was included in the good category. The results of the hypothesis analysis using the t-test showed that the resulting value was higher than the 5% significance level, which led to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (H0). Thus, it can be stated that the use of the Microblogging Threads platform has a significant influence on students' ability to write argumentative texts. This media has proven effective in helping students develop ideas, organize arguments logically, and increase their learning motivation.